Nilai Maslahah Reksadana Syariah dalam Perspektif Maqashid Syariah - Syintia Amanda Rhetha; Yenita Karisha; Nurris Kiyani; Tri Noviantika Zain; Muhammad Taufiq Abadi (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
The relationship between Maqasid Syariah and Maslahah is very close, because the purpose of Maqasid Syariah itself is to achieve the benefit of the people. This study aims to describe the values of maslahah contained in the investment activities of Islamic mutual funds. This study uses qualitative methods through the study of literature. Data collection techniques are carried out by searching for relevant library materials, then studying them and analyzing them in depth so that they can support the statements that have been presented. The development of the Islamic capital market, which shows a positive trend in its growth, certainly provides new hope for a more stable Indonesian economy. The benefits of Sharia mutual funds in the perspective of Maqashid Syariah include mutual funds as halal investment instruments and mutual funds as the realization of the ta'awun principle. The challenge of Sharia mutual fund development in Indonesia is the low literacy of the community towards Sharia-based investment products. But when viewed from its growth, Islamic finance has a great opportunity to grow in Indonesia.